Runx1 is expressed in adult mouse hematopoietic stem cells and differentiating myeloid and lymphoid cells, but not in maturing erythroid cells. - North, T; Stacy, T; Matheny, C; Speck, N; de Bruijn, M (2004)
The transcription factor Runx1 marks all functional hematopoietic stem cells (HSCs) in the embryo and is required for their generation. Mutations in Runx1 are found in approximately 25% of acute leukemias and in familial platelet disorder, suggesting a role for Runx1 in adult hematopoiesis as well. A comprehensive analysis of Runx1 expression in adult hematopoiesis is lacking. Here we show that Runx1 is expressed in functional HSCs in the adult mouse, as well as in cells with spleen colony-forming unit (CFU) and culture CFU capacities. Additionally, we document Runx1 expression in all hematopoietic lineages at the single cell level. Runx1 is expressed in the majority of myeloid cells and in a smaller proportion of lymphoid cells. Runx1 expression substantially decreases during erythroid differentiation. We also document effects of reduced Runx1 levels on adult hematopoiesis.